2017
DOI: 10.1177/1077558717747985
|View full text |Cite
|
Sign up to set email alerts
|

Development and Initial Validation of the Caregiver Perceptions About Communication With Clinical Team Members (CAPACITY) Measure

Abstract: Despite the important role that family caregivers play managing the care of persons with complex health needs, little is known about how caregivers perceive themselves to be recognized and valued by health care professionals. Our objective was to develop and validate a novel measure, the CAregiver Perceptions About Commun Ication with Clinical Team members (CAPACITY) instrument. Questions focus on perceived quality of communication with the health care team and the extent to which caregivers believe that the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 49 publications
1
39
0
Order By: Relevance
“…In this study, 40% of respondents regularly inquired about caregivers' ability to provide assistance and need for services or supports, but nearly 20% almost never asked about these issues. Surveys of family caregivers indicate that large proportions are never asked by health care providers about their abilities and preferences, 39 whether they need help managing older adults' care, 17 or what they need to take care of themselves 18 . The vast majority report that they do not receive role‐related training 10 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 40% of respondents regularly inquired about caregivers' ability to provide assistance and need for services or supports, but nearly 20% almost never asked about these issues. Surveys of family caregivers indicate that large proportions are never asked by health care providers about their abilities and preferences, 39 whether they need help managing older adults' care, 17 or what they need to take care of themselves 18 . The vast majority report that they do not receive role‐related training 10 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, CSP has partnered with the Office of Rural Health to help address some of the unique access needs of rural caregivers. In addition, primary care provider referrals for caregiver support is one potential area of improvement within VA. Van Houtven et al (2017) illustrated that caregivers perceive providers as rarely considering their capacity for providing high quality of care or seeking their input on the veteran’s care plan. Thus, improving caregiver and provider communication could have multiple benefits, more efficiently linking caregivers to supportive services and more effectively incorporating caregiver expertise into the veteran’s plan of care.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the quantitative results should be interpreted with caution due to a low survey response rate and item missingness—31% missing on average per item—which warrants further investigation: In this study, these data are meant to be interpreted in conjunction with qualitative findings. This was an observational study designed to shed light on use and value of program services, and future research could test the relationship of potential mechanisms identified in this study and based on the Organizing Framework for Caregiver Interventions with caregiver and patient outcomes (Van Houtven et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, care partners reported their relationship to the patient and answered questions from the communication domain from the CAPACITY instrument. The CAPACITY instrument is a validated measure of Caregiver Perceptions About Communication with Clinical Team members [23]. The instrument measures caregivers' perceptions of care team interactions in two domains: quality of communication with the health care team and health care team's consideration of the care partner's capacity and preferences for caregiving.…”
Section: Methodsmentioning
confidence: 99%